Risk evaluation of rural financial organization operation based on the BP - Fan, S.; Zhao, Y.; Xie, H.; Li, C. (Journal of Digital Information Management, 2012)
The rural financial organization plays an important role in promoting the healthy development of the national economy especially the development of the rural economy. However, the rural financial organization risk especially the operating risk is still an outstanding problem. It has become a big obstacle in new countryside development. In this paper we analyzes the rural financial organization operational risk index firstly, then use these index as the input data for the BP neural network. After that we modeling rural financial organization operational risk early warning based the BP neural network. At last we take an experiment on a rural somewhere, the result shows that the BP neural network can reflect of the operation risk of the rural financial organization quickly and accurately.
Keywords: BP Neural Network; Risk early warning; Risk evaluation; Rural finanical